Human SWI/SNF-Associated PRMT5 Methylates Histone H3 Arginine 8 and Negatively Regulates Expression of ST7 and NM23 Tumor Suppressor Genes - Pal, Sharmistha (American Society for Microbiology, 2004)
Protein arginine methyltransferases (PRMTs) have been implicated in transcriptional activation and repression, but their role in controlling cell growth and proliferation remains obscure. We have recently shown that PRMT5 can interact with flag-tagged BRG1- and hBRM-based hSWI/SNF chromatin remodelers and that both complexes can specifically methylate histones H3 and H4. Here we report that PRMT5 can be found in association with endogenous hSWI/SNF complexes, which can methylate H3 and H4 N-terminal tails, and show that H3 arginine 8 and H4 arginine 3 are preferred sites of methylation by recombinant and hSWI/SNF-associated PRMT5. To elucidate the role played by PRMT5 in gene regulation, we have established a PRMT5 antisense cell line and determined by microarray analysis that more genes are derepressed when PRMT5 levels are reduced. Among the affected genes, we show that suppressor of tumorigenicity 7 (ST7) and nonmetastatic 23 (NM23) are direct targets of PRMT5-containing BRG1 and hBRM complexes. Furthermore, we demonstrate that expression of ST7 and NM23 is reduced in a cell line that overexpresses PRMT5 and that this decrease in expression correlates with H3R8 methylation, H3K9 deacetylation, and increased transformation of NIH 3T3 cells. These findings suggest that the BRG1- and hBRM-associated PRMT5 regulates cell growth and proliferation by controlling expression of genes involved in tumor suppression.